Reinterpretasi Kaba Cindua Mato dalam Perspektif Kitab Salasilah Raja-raja di Minangkabau - Kurnia, Sultan; Permana, Zera; Soares, Ghio V.D.; Nasri, Daratullaila (Tambo: Journal of Manuscript and Oral Tradition, 2025)
This study reinterprets Kaba Cindua Mato (KCM) by comparing the Hikayat Tuanku Nan Muda Pagaruyung (HTNMP) from the Leiden University Library with newly discovered data from the Kitab Salasilah Raja-Raja di Minangkabau (KSRRM). Using a narrative comparative approach, the analysis focuses on four main aspects: characters, genealogy, plot structure, and conflict. Based on this comparison, the study reveals that the core narrative in both texts remains similar, particularly regarding the conflict between the Pagaruyung Kingdom and the Sungai Ngiang Kingdom. However, there are fundamental differences in character names, genealogical backgrounds, and historical chronology, especially concerning the parents of Bundo Kandung and the father of Dang Tuanku. This reinterpretation further reinforces previous researcher’s assumptions that Kaba Cindua Mato (KCM) is not merely an oral folk tale, but also a kaba composed with a strong historical foundation rooted in the era of the Minangkabau kings from the late 15th to the early 16th century CE. The findings of this study cntribute to a deeper understanding of the meaning of Kaba Cindua Mato, while also enriching knowledge of Minangkabau history.